Nationalism Studies Applied to a Register of Mexican Colonial Translations. Interim Report - Payàs, Gertrudis (TTR)

(untitled) (Association canadienne de traductologie, 2005)
AbstractTo study translation as a representation of the Mexican nation on the basis of a catalogue of translations spanning three centuries, I propose a classification method inspired by some concepts of nationalism studies. I will try to contribute an analysis of the possible ways of handling such a catalogue while stressing the importance of classifications. I will also highlight the interest of establishing a dialogue between translation studies and other disciplines, such as nationalism studies.